Generalized Hyers-Ulam-Rassias Theorem in Menger Probabilistic Normed Spaces - M. Eshaghi Gordji; M. B. Ghaemi; H. Majani (Discrete Dynamics in Nature and Society)
We introduce two reasonable versions of approximately additive functions in a Šerstnev probabilistic normed space endowed with Π𝑀 triangle function. More precisely, we show under some suitable conditions that an approximately additive function can be approximated by an additive mapping in above mentioned spaces.